An envelope method for analysing sequential pattern formation - Cruywagen, G; Maini, P; Murray, J (2000)
We examine sequential spatial pattern formation in a tissue interaction model for skin organ morphogenesis. Pattern formation occurs as a front sweeps across the domain leaving in its wake a steady state spatial pattern. Extensive numerical simulations show that these fronts travel with constant wave speed. By considering the envelope of the solution profile we present a novel method of calculating its wave speed.